Distributional Goals and Optimal Growth - Stanley, Owen (Review of Economic Studies, 1978)
Journal Article Distributional Goals and Optimal Growth Get access Owen Stanley Owen Stanley Australian National University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 389–390, https://doi.org/10.2307/2297355 Published: 01 June 1978 Article history Received: 01 February 1976 Accepted: 01 April 1977 Published: 01 June 1978